Effect of Dietary Extract of Thyme and Vitamin E Supplementation on Immune Responses and Yolk Cholesterol in Laying Hen under Heat Stress Condition - O Tahmasbi; F Shariatmadari; MA Karimi Torshizi (Institue of Medicinal Plants, ACECR, 2012)
Background : Thyme extract had shown to have antimicrobial and autoxidative activities. It is claimed that it causes reduction in serum cholesterol and improves immune system.   Objective : An experiment was conducted to investigate the effect of dietary Thyme extract on serum cholesterol, yolk cholesterol and immune system under heat stress in laying hens.   Methods : for six weeks with 108 hens from Lohman strain of 45 weeks old. The experiment had a 2× 2 × 3 factorial arrangement. Treatments include cyclic hot and neutral temperature, two fat sources of saturated and unsaturated and tree experimental treatments of control group (without additive), vitamin E and thyme extract. To determine the factors which affect on antibody production, the Sheep Red Blood Cell (SRBC) was injected on the day 30 and 37 following the start of experiment .   Results : Statistical analysis has shown a significant increase differences between the level of serum cholesterol and yolk cholesterol significantly under heat stress (p<0.05). Saturated fat significantly increased yolk cholesterol (p<0.05). However, thyme treatment decreased serum and yolk cholesterol (p<0.05). In addition, temperature had significant effect on first and second antibody titer (p<0.05). Furthermore, in second SRBC injection, thyme had the highest significant effect on antibody increment (p<0.05). Conclusion : Phenolic compounds within thymol reduced serum cholesterol and improved immune response especially in high environment temperature.